'Getting better bit by bit': Exploring learners' enactments of student voice in physical education. Issue 1 (2nd January 2021) - Howley, Donal; O'Sullivan, Mary
ABSTRACT: Guided by Dewey's [1966. Democracy and education . New York: The Free Press] concept of 'education as growth', the purpose of this paper is to explore learners' enactments of student voice in Physical Education (PE) at a time of curricular reform. A qualitative comparative case study design gathered data from 18 students across 10 months in a triad of Irish secondary schools using focus group interviews. Data were gathered and coded to identify emergent themes. Five experiential themes emerged: puppeteering; early enlightenment; enjoyment in living; equitable inquiry and critique; and learning to grow. Findings demonstrate how student voice encounters were necessary to enhance students' democratic experience of PE but the extent to which student voice was enacted to improve learning and assessment of curriculum was problematic for students to assert. Implementing student voice cannot be perceived and implemented as a fixed process but rather a fluid continuum of practice allowing more transformative experiences follow.